Androgen levels in autism spectrum disorders: a systematic review and meta-analysis - Wang, Zhao; Zhang, Bohan; Mu, Chenyu; Qiao, Dan; Chen, Huan; Zhao, Yan; Cui, Huixian; Zhang, Rong; Li, Sha (Frontiers in Endocrinology, 2024)
Background Accumulating evidence suggests that the autism spectrum disorder (ASD) population exhibits altered hormone levels, including androgens. However, studies on the regulation of androgens, such as testosterone and dehydroepiandrosterone (DHEA), in relation to sex differences in individuals with ASD are limited and inconsistent. We conducted the systematic review with meta-analysis to quantitatively summarise the blood, urine, or saliva androgen data between individuals with ASD and controls. Methods A systematic search was conducted for eligible studies published before 16 January 2023 in six international and two Chinese databases. We computed summary statistics with a random-effects model. Publication bias was assessed using funnel plots and heterogeneity using I2 statistics. Subgroup analysis was performed by age, sex, sample source, and measurement method to explain the heterogeneity. Results 17 case-control studies (individuals with ASD, 825; controls, 669) were assessed. Androgen levels were significantly higher in individuals with ASD than that in controls (SMD: 0.27, 95% CI: 0.06–0.48, P=0.01). Subgroup analysis showed significantly elevated levels of urinary total testosterone, urinary DHEA, and free testosterone in individuals with ASD. DHEA level was also significantly elevated in males with ASD. Conclusion Androgen levels, especially free testosterone, may be elevated in individuals with ASD and DHEA levels may be specifically elevated in males.